2009
DOI: 10.1097/fjc.0b013e318199f30b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Treatment with Angiotensin II Type 1 Receptor Blocker and Statin on Stent Restenosis

Abstract: Angiotensin II type I receptor blocker (ARB) or statin has been reported to be effective in preventing stent restenosis, but little is known about the combined effect on stent restenosis. The objective of this study was to determine the effect of combination therapy with ARB and statin on restenosis rate after coronary stenting and on proliferation and migration of and reactive oxygen species (ROS) production by human coronary artery smooth muscle cells (SMCs) in vitro. Clinical data were collected from 330 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…16 ARBs also play a role in three mechanisms that may prolong access patency: promoting venous dilation, 17,18 preventing platelet activation, 19,20 and inhibiting neointimal hyperplasia. [21][22][23][24][25][26][27][28][29] Our data suggest that the association of ARB with autogenous AV access patency is potentiated by use of antiplatelet medication. Improved autogenous access patency may rely on the combined effects of ARB-induced venous dilation and prevention of stenosis and antiplatelet inhibition of platelet function.…”
Section: Discussionmentioning
confidence: 80%
“…16 ARBs also play a role in three mechanisms that may prolong access patency: promoting venous dilation, 17,18 preventing platelet activation, 19,20 and inhibiting neointimal hyperplasia. [21][22][23][24][25][26][27][28][29] Our data suggest that the association of ARB with autogenous AV access patency is potentiated by use of antiplatelet medication. Improved autogenous access patency may rely on the combined effects of ARB-induced venous dilation and prevention of stenosis and antiplatelet inhibition of platelet function.…”
Section: Discussionmentioning
confidence: 80%
“…1) (47, 60, 72). Therefore, it has been proposed that a combined therapy with statins or PPAR agonists and RAAS blockers to target multiple therapeutic pathways might provide the optimal treatment (14,47,119).…”
Section: Combination Therapy To Overcome Unwanted Metabolic Effects Omentioning
confidence: 99%
“…Sixteen of these studies were excluded for the following reasons: three of them were not clinical trials; [1,2,4] three of them compared different types or dosages of ARBs rather than comparing the risks with and without an ARB; [5][6][7] four studies provided none of the outcomes of interest; [8][9][10][11] two studies reported only stent number and not patient number; [12,13] the other four studies were excluded because they were not randomized controlled trials. [14][15][16][17] Finally, five studies with a total number of 624 patients met the inclusion criteria [18][19][20][21][22] (figure 1).…”
Section: Resultsmentioning
confidence: 99%